Chemical Vapour Deposition An Integrated Engineering Design for Advanced Materials - Xu, Yongdong; Yan, Xiu-Tian.; SpringerLink (Online service) (London : Springer London, 2010)
The rapid advancement in chemical vapour deposition (CVD) technology has reached many fields of application, including thin film coating, microelectronics and communications. Chemical Vapour Deposition: An Integrated Engineering Design for Advanced Materials focuses on the application of this technology to engineering coatings and, in particular, to the manufacture of high performance materials, such as fibre reinforced ceramic composite materials, for structural applications at high temperatures. While previous discourses on CVD have had a tendency to focus solely on electronics, this book aims to provide a thorough exploration of the design and applications of advanced materials, and their manufacture in engineering. It addresses a wide range of topics related to CVD theories and applications. From physical fundamentals and principles, to optimisation of processing parameters and other current practices, this book is designed to guide readers through the development of both high performance materials and the design of CVD systems to manufacture such materials. Chemical Vapour Deposition: An Integrated Engineering Design for Advanced Materials introduces integrated design and manufacture of advanced materials to researchers, industrial practitioners, postgraduates and senior undergraduate students. It also features a large body of appendices to provide references for further study. The Engineering Materials and Processes series focuses on all forms of materials and the processes used to synthesise and formulate them as they relate to the various engineering disciplines. The series deals with a diverse range of materials: ceramics; metals (ferrous and non-ferrous); semiconductors; composites, polymers, biomimetics etc. Each monograph in the series is written by a specialist and demonstrates how enhancements in materials and the processes associated with them can improve performance in the field of engineering in which they are used.
to Chemical Vapour Deposition -- Physical Fundamentals of Chemical Vapour Deposition -- Chemical Vapour Deposition Systems Design -- Thermodynamics and Kinetics of Chemical Vapour Deposition -- Chemical Vapour Infiltration -- Microstructure Evolution and Process Control.
Keywords: Engineering; Structural control (Engineering).; Materials; Engineering; Operating Procedures, Materials Treatment; Materials Science, general